Automobile axle accelerations statistical analysis of field measurements - Stayner, R. M. (College of Aeronautics)
Summary Accelerations produced at the stub-axles of a vehicle during passage over a road surface are a prominent source of vibrations of the vehicle. This memo describes the instrumentation of a motor car to record these accelerations, and the statistical analysis of records obtained, in terms of Amplitude Distribution, Power Spectral Density Function and Auto.. correlation Function. Cross-correlation functions between some of the acceleration signals are included and their salient features discussed, together with the utility of the other statistical descriptions. Sugr4estions are made for laboratory work to increase the information to be gained from such measurements and the generality with which it can be applied.